Formations of belief : historical approaches to religion and the secular - Nord, Philip G., 1950-; Guenther, Katja; Weiss, Max, 1977- (Princeton University Press, 2019)
This book offers a more nuanced understanding of the origins of secularist thought, demonstrating how Reformed Christianity and the Enlightenment were not the sole vessels of a worldview based on rationalism and individual autonomy.